Assessment of Complications Secondary to Silicone Oil Injection after Pars Plana Vitrectomy in Rhegmatogenous Retinal Detachment in Early Post Operative Phase - , Aziz-ur-Rehman, Nasir Bhatti, Mazhar-ul-Hassan, Asif Kazi,Umair Qidwal (Pakistan Journal of Ophthalmology, 2011)
Purpose: To assess the postoperative complications of silicone oil injection after pars plana vitrectomy in rhegmatogenous retinal detachment. Materials And Method: The study was carried out at vitreo-retinal unit of Al- Ibrahim Eye Hospital, from January 2009 to June 2009. 100 eyes with rhegmatogenous retinal detachment according to inclusion and exclusion criteria were included in the study. Results: Out of 100 patients included in the study, 43 had raised intraocular pressure, while the rest of 57 patients did not show any rise in intraocular pressure after three months of follow up, all 100 (100%) patients developed some form of change in their refractive status, only 6 (6%) patients developed band keratopathy till 3rd month of follow up, while only 8 (8%) had silicone oil emulsification in their eye in 3 month follow ups. Conclusion: Raised intraocular pressure and change in refractive status were the two most common complications seen in our study; both of these complications can be managed easily.